Predictive Stator Flux and Load Angle Control of Synchronous Reluctance Motor Drives Operating in a Wide Speed Range - Hadla, Hazem (2020)
This paper presents a new simplified finitecontrol- set model predictive control strategy for synchronous reluctance motors operating in the entire speed range. It is a predictive control scheme that regulates the stator flux and the load angle of the synchronous reluctance motor, incorporating the ability to operate the drive in the field-weakening region and respecting the motor voltage and current limits as well as the load angle limitation needed to operate this type of motor in the maximum torque per voltage region. The proposed control strategy possesses some attractive features, such as no need for controller calibration, no weighting factors in the cost function, good robustness against parameter mismatch, and smaller computational cost compared to more traditional finite-control-set model predictive control algorithms. Simulation and experimental results obtained using a high-efficiency synchronous reluctance motor demonstrate the effectiveness of the proposed control scheme.